Role of Left Atrial Strain Using Two-Dimensional Speckle Tracking Echocardiography for Early Detection of Left Ventricular Diastolic Dysfunction in Patients with Preserved Left Ventricular Ejection Fraction - Ali, Syed Mahmud; Haque, Tuhin; Hassan, Md. Rashidul; Rahman, Faria; Latif, Sayem Bin; Mostafa-Al-Rasel, Md.; Hasan, Md. Kamrul; Shafi-Ul-Alam, Md.; Khan, Md. Faisal Bin Selim (Cardiology and Cardiovascular Medicine, 2025)
Background: Left ventriculardiastolic dysfunction (LVDD) evaluation is challenging and difficult by using current conventional echocardiogram. Increased left atrial volume index (LAVI) is one of the established parameter of left ventricular diastolic dysfunction, but mainly reflect the chronic effect of raised left ventricular filling pressure. Recent studies have suggested that left atrial (LA) strain could be animportant criteriafor early assessment of left ventriculardiastolic dysfunction. Considering left atrial strain along with left atrial volume index could raise the detection of left ventriculardiastolic dysfunction, however it is not yet proved. Objectives: The study was done to analyze the importance of left atrial strain for early detection of left ventricular diastolic dysfunction and whether adding left atrial strain to left atrial volume index could raise the rate of detection of left ventricular diastolic dysfunction in patients with preserved left ventricular ejection fraction (LVEF). Methods: Using two-dimensional echocardiography, color Doppler imaging, tissue Doppler imaging and 2-dimensional speckle-tracking echocardiography, we analyzed a population of 52 patients in sinus rhythm at risk for left ventricular diastolic dysfunction such as those with systemic hypertension, diabetes mellitus, obesity, dyslipidemia or chronic coronary syndrome with preserved left ventricular ejection fraction. Results: The study showed significant association of left atrial strain withabnormal septal e’ or lateral e’, (p<0.05), which are established parameters of left ventricular diastolic dysfunction. This study also showed, in patients with estimated elevated left ventricular filling pressures(E/e’>14), the rate of abnormal left atrialstrain was significantly higher than an abnormal left atrial volume index (100% vs. 45.5%, p <0.05). Here also in patients with normal left atrial volume index, otherleft ventricular diastolic dysfunction parameters like E/e’>14, TRVmax > 2.8 m/sand abnormal left atrial strain were present (13.6% had E/ e’ >14,6.8% had TRVmax >2.8 m/s and 38.6% had abnormal left atrial strain, p<0.05). Left atrial strain showed sensitivity of 54.5%, specificity of 100%, positive predictive value of 100% and accuracyof 61.5%. So, Left atrial strain could be used as a diagnostic tool for left ventricular diastolic dysfunction, and left atrial strain helps for early detection ofleft ventricular diastolic dysfunction (p <0.5). Conclusion: Thefindings of the study showed that left atrial strain can be used for early detection of left ventricular diastolic dysfunction and adding left atrial strain to left atrial volume index increases the rate of detection of left ventricular diastolic dysfunction.